The Book of Judges - Webb, Barry G. (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2012)
The book discusses not only unique features of the stories themselves but also such issues as the violent nature of Judges, how women are portrayed in it, and how it relates to the Christian gospel of the New Testament. --from publisher description.
Introduction. Judges as an Israelite classic -- The period of the Judges in Israel's history -- The history of the book's formation -- It's shape and content -- Recent scholarly study of Judges -- Its contribution to Old Testament theology -- Judges as Christian scripture -- The text -- The translation -- Select bibliography -- Text and Commentary. Introduction (1:1-3:6) -- Careers of the judges (3:7-16:31) -- Epilogue (17:1-21:25).
Includes bibliographical references and index.
Description based on print version record.
Keywords: Bible. -- Commentaries; RELIGION / Biblical Studies / Old Testament; Electronic books